2009
DOI: 10.3139/146.110234
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of Ti-alloys by SPD processing to achieve superior fatigue properties

Abstract: This work is related to the enhancement of the fatigue properties in ultrafine-grained Ti alloys produced by severe plastic deformation techniques. To process commercially pure Ti Grade 4 and Ti-6Al-4V alloys, combined severe plastic deformation techniques that include equal channel angular pressing and additional thermal and deformation treatments were used. As a result we could produce ultrafine-grained Ti materials with a similar grain size of less than 300–400 nm but different in their shape and grain boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 26 publications
0
39
1
Order By: Relevance
“…A final one-hour annealing was imposed at 773 K for reducing the internal elastic stresses without inducing significant growth of the grains [5,20]. The state produced by ECAP and extrusion will be further referred to as «UFG1».…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…A final one-hour annealing was imposed at 773 K for reducing the internal elastic stresses without inducing significant growth of the grains [5,20]. The state produced by ECAP and extrusion will be further referred to as «UFG1».…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…Several reports are now available describing the processing of pure Ti by ECAP [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and HPT [24][25][26] and there are also some reports on the processing of the Ti-6Al-4V alloy by ECAP [27][28][29][30] and HPT [31][32][33][34]. Nevertheless, a review of these data shows that all of the experiments were conducted using commercial Ti-6Al-4V alloys that were processed in the hot-rolled or extruded condition.…”
Section: Introductionmentioning
confidence: 93%
“…A corrosion study reported superior corrosion resistance in UFG Ti due to rapid passivation along the grain boundaries (Balyanov et al, 2004). The fatigue life of Ti is enhanced by SPD so that in Grade 4 Ti the fatigue limit after 10 7 cycles was increased to $590 MPa using ECAP compared with $350 MPa in the coarse-grained (CG) condition (Semenova et al, 2008(Semenova et al, , 2009Estrin and Vinogradov 2010). Recent research on biocompatibility has documented improved pre-osteoblast attachment and rate of growth on UFG pure Ti compared with CG pure Ti and Ti-6Al-4V substrates, where this is attributed to the presence of surface discontinuities, the surface energy, a higher wettability and the presence of stable TiO 2 films which improve the protein adsorption on the surface (Faghihi et al, 2007;Park et al, 2009;Bindu et al, 2009).…”
Section: Introductionmentioning
confidence: 98%